THE INFLUENCE OF LINE EXTENSION STRATEGIES BY PREMIUM BRANDS ON BRAND EQUITY: CULTURAL DIFFERENCES BETWEEN GERMANY AND THAILAND - Florian Lukas SEIZER (Management & Marketing)
Premium markets are expected to outperform other markets throughout the near future. Thus these markets are of high importance for marketers, who already face challenges to manage premium brands due to the hazard of a possible dilution of user’s sense of exclusivity and pride. Premium brand managers must know when it is best to take a pass on short-term growth opportunities that could tarnish the brand's long-term health. Line extensions embody one of the most frequently used vehicles for growth to meet global consumer needs. Though they have advantages, also risks are associated with them. Consequently, the purpose of this study is to identify the influence of line extensions on brand equity in culturally different spheres. The study focuses on premium brands from the automotive industry and asks if and in how far different – vertical (different price & quality level) and horizontal (same price & quality level) – line extension strategies influence brand equity differently among cultures. A one group pre-test post-test research design is used to measure brand equity before and after an existing brand’s (hypothetical) extension. A structured online survey with page logic collected primary data from four hundred students in Germany and Thailand recruited by a matched sampling technique. Culture has to be added to brand equity models as results show distinctive changes of brand equity for both Germany and Thailand. While after vertical downscale extensions, brand equity increases in Germany, it decreases in Thailand. Hence, the research results in managerial recommendations which assess if product policy strategies should be thought ‘regionally’ or ‘globally’.